Critical Conditions and Energy Transfer Characteristics of the Failure Process of Coal-Rock Combination Systems in Deep Mines. (25th February 2021) - Sun, Haitao; Dai, Linchao; Liu, Yanbao; Jin, Hongwei
Abstract : With the steady increase in the size, intensification, and modernization of coal production enterprises, the deep coal resources in large coal bases are gradually entering the mining stage. When the coal mining reaches the deep zone, the interactions between various underground dynamic hazards begin to occur. These interactions are affected by the engineering geological environment and can lead to the occurrence of severe compound hazards. When coal and gas outbursts occur and destabilize the mining area, the high geostress causes the multiphysical coupling effect of the laminated overburden system to become more pronounced. Therefore, we analyzed the development path of a coal-rock system under instability conditions from the perspective of coal–rock coupling, constructed a model of the coal-rock combination system's structure, and proposed three directions (i.e., strain softening, limit equilibrium, and dynamic instability) for the development of coal-rock system instability. Then, we established a model for the critical conditions of the system's failure process and elucidated that the release of the rock's elastic energy promoted the instability of the coal. Furthermore, we verified the established critical conditions through laboratory tests on a coal-rock combination structure and obtained the patterns of the rock energy transferring into the coal seam during the instability failure process of the coal–rock combination structure. When the coal–rock combination structure failed, the rock strain reached its maximum value and the strain rebound phenomenon occurred. The stored elastic strain energy released by the rock into the combination system accounted for 26% to 53% of the accumulated energy in the rock itself, and the released elastic energy and the new surface area of the crushed coal sample followed a logarithmic relationship. The findings of this study provide theoretical support for the identification and quantitative analysis of instability due to the dynamic hazards of coal-rock gas in deep mines.